2022
DOI: 10.4314/ahs.v22i4.50
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions about non-communicable diseases by people living with HIV: a descriptive cross-sectional study from Chitungwiza Central Hospital Zimbabwe

Abstract: Background: Sub-Saharan Africa has shown a rise in morbidity and mortality due to NCDs. PLHIV have shown to be more exposed to NCDs and identifying the knowledge gaps might help the management of NCDs in PLHIV. Objective: The study was conducted in order to determine knowledge and perceptions regarding NCDs in PLHIV from Chitungwiza Hospital. Methods: This was a cross-sectional survey on 324 participants from Chitungwiza Hospital. Data collection was through a designed questionnaire. Knowledge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…People with a formal education may have higher knowledge about HTN and thus adopt and maintain its preventive measures and may perceive being at low risk. Relatedly, among people living with HIV in Chitungwiza Hospital Zimbabwe, having low education level (primary or less) was associated with negative perception about NCD management compared to those with higher education (P<0.01) [26]. On the otherhand, a study by Cioe et al [27] found that knowledge of HTN risk factors did not predict perceived risk for HTN among PLHIV in Rhode Island Hospital -USA (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…People with a formal education may have higher knowledge about HTN and thus adopt and maintain its preventive measures and may perceive being at low risk. Relatedly, among people living with HIV in Chitungwiza Hospital Zimbabwe, having low education level (primary or less) was associated with negative perception about NCD management compared to those with higher education (P<0.01) [26]. On the otherhand, a study by Cioe et al [27] found that knowledge of HTN risk factors did not predict perceived risk for HTN among PLHIV in Rhode Island Hospital -USA (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This includes papers on cancer [1][2][3][4][5][6][7][8][9][10][11][12] ; diabetes mellitus [13][14][15][16] ; surgery [15][16][17][18][19][20][21][22][23][24][25] ; other non-communicable diseases [26][27][28][29][30][31][32][33] , as well as sexual reproductive health [34][35][36][37][38][39][40][41][42][43][44][45][46] . The menu continues with HIV / AIDS papers [47][48][49][50][51][52][53][54] . This is appropriate because 1 st December is World AIDS Day and countries in Sub Saharan Africa have little to celebrate as new infections and needless deaths continue in the face of global and local financial challenges.…”
mentioning
confidence: 99%